1997
DOI: 10.1007/bf01285555
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of 1-methyl-4-phenylpyridinium (MPP+) neurotoxicity by deprenyl in organotypic canine substantia nigra cultures

Abstract: Systemic administration of MPTP to experimental animals induces neurodegeneration of dopaminergic neurons in the central nervous system. MPTP crosses the blood-brain barrier where it is taken up by astrocytes and converted to MPP+ by monamine oxidase-B (MAO-B). Subsequently, MPP+ is selectively taken up by dopaminergic neurons upon which it exerts intracellular neurotoxic effects. Systemic administration of the selective MAO-B inhibitor deprenyl prevents the conversion of MPTP to MPP+ and by this mechanism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The present findings confirm our preliminary in vivo report (Wu et al, 1993b) and agree with several in vitro studies which indicate that deprenyl can protect against spontaneous cell death and MPP + toxicity in primary cultures of midbrain dopaminergic neurons (Mytilineou and Cohen, 1985;Roy and Bedard, 1993;Schmidt et al, 1993;Vizuete et al, 1993). The present in vivo study demonstrates that deprenyl can provide significant protection against MPP + toxicity when the nigral injury caused by the toxic MPTP metabolite is less than 50% as indicated by dopamine deficiency in the striatum (Fig.…”
Section: Discussionsupporting
confidence: 95%
“…The present findings confirm our preliminary in vivo report (Wu et al, 1993b) and agree with several in vitro studies which indicate that deprenyl can protect against spontaneous cell death and MPP + toxicity in primary cultures of midbrain dopaminergic neurons (Mytilineou and Cohen, 1985;Roy and Bedard, 1993;Schmidt et al, 1993;Vizuete et al, 1993). The present in vivo study demonstrates that deprenyl can provide significant protection against MPP + toxicity when the nigral injury caused by the toxic MPTP metabolite is less than 50% as indicated by dopamine deficiency in the striatum (Fig.…”
Section: Discussionsupporting
confidence: 95%
“…, 2006). Changes of endogenous dopamine (DA) and/or DA metabolite levels in growing cultures with or without neurotrophic factors and depletion by neurotoxic treatments have also been reported in such cultures (Schmidt et al. , 1997; Gramsbergen et al.…”
Section: Introductionmentioning
confidence: 97%
“…The study showed that (-)-deprenyl could reduce dopaminergic neuronal death at a step beyond the conversion of MPTP to MPP + by MAO-B. Subsequently, a number of investigations using a variety of approaches have unequivocally established that (-)-deprenyl can reduce neuronal death independently of MAO-B or MAO-A inhibition (Ansari et al, 1993;Finnegan et al, 1990;Gelowitz and Paterson, 1999;Le et aI., 1997a;Schmidt et al, 1997;Tatton and Chalmers-Redman, 1996;Tatton and Greenwood, 1991). According to these results, MAO-B inhibition is not necessary for (-)-deprenyl to reduce neuronal death and raises the question as to whether any of the clinical slowing found in PD patients treated with (-)-deprenyl resulted from MAO-B independent neuronal rescue.…”
Section: Gapdh As a Mediator Of Neuronal Apoptosismentioning
confidence: 95%
“…The models have included neuronal death induced by 6-hydroxydopamine (Salonen et al, 1996), MPP + (Koutsilieri et al, 1996;Koutsilieri et al, 1994;Le et al, 1997a;Mytilineou and Cohen, 1985;Schmidt et al, 1997;Tatton and Greenwood, 1991;Vizuete et al, 1993;Wu et al, 1995); MPTP (Cohen et al, 1984;Fuller et al, 1988;Takada et al, 1993;Tatton and Greenwood, 1991), nitric oxide or peroxynitrite (Maruyama et al, 1998), DSP-4 (Finnegan et aI., 1990;Yu et al, 1994;Zhang and Yu, 1995); glutathione depletion (Mytilineou et al, 1998), peripheral nerve crush or axotomy (Ansari et al, 1993;Iwasaki et al, 1996;Ju et al, 1994;Oh et al, 1994;Salo and Tatton, 1992); optic nerve crush (Buys et al, 1995); hypoxia and/or ischemia (Knollema et al, 1995;Lahtinen et al, 1997;Paterson et al, 1997 ;Ravikumar et al, 1998;Semkova et al, 1996); cytosine arabinoside (Paterson et al, 1998); excitotoxins (Gelowitz and Paterson, 1999;Mytilineou et al, 1997;Pereira and Oliveira, 1997;Semkova et al, 1996), trophic insufficiency (Ragaiey et al, 1997;Tatton et al, 1994;Wadia et al, 1998); thiamine deficiency (Tod...…”
Section: Gapdh As a Mediator Of Neuronal Apoptosismentioning
confidence: 99%